PENAMBAHAN TEPUNG BUNGA KECOMBRANG (Nicolaia spesiosa Horan) SEBAGAI BAHAN PENGAWET ALAMI DALAM MEMPERPAJANG DAYA SIMPAN CUKO PEMPEK - Eka Putra, Aan Novianus; Suyatno, Suyatno; Alhanannasir, Alhanannasir (Universitas Muhammadiyah Palembang, 2014)
The purpose of this research is to study the addition of flour kecombrang interest (Nicolaia spesiosa Horan) as a natural preservative in extending the shelf life cuko pempek. This research has been carried out in the Laboratory Alhamdulillah Faculty of Agriculture, University of Muhammadiyah Palembang April to August, 2014. This research method is experiment using a Rancangan Acak Kelompok (RAK). Factors adding flour research interest kecombrang (C) arranged in nonfaktorial which consists of four (4) treatment and repeated 4 (four) times. Each treatment with starch concentration kecombrang interest as much as 0%, 1%, 2% and 3%. The parameters observed in this study, for chemical analysis include total acid and pH levels before and after 12 days of storage, while the organoleptic tests include color, flavor and flavor in cuko pempek before and after storage for 12 days as well as physical observations done visually by looking signs of froth and viscosity changes during storage cuko pempek. Observations were made with a 3-day intervals until day 12. The results showed that the addition of flour kecombrang interest as a natural preservative very significant effect on the total acid before and after 12 days of storage, significantly affect the pH cuko pempek before storage of 12 days and a very significant effect on pH cuko pempek after 12 days of storage. Organoleptic test results showed that the addition of flour kecombrang not significant interest to the color before and after 12 days of storage, no real effect on the taste cuko pempek before storage of 12 days and significantly affect the taste cuko pempek after 12 days of storage and significantly affect the flavor cuko pempek before and after 12 days of storage. Test results storability by visual observation of the presence or absence of foam and viscosity changes during storage at cuko pempek 12 days on C3 treatment after 12 days of storage froth and yet there have been no changes in the viscosity of cuko pempek.